Studies in law, politics, and society - Sarat, Austin (Bingley, United Kingdom : Emerald Publishing Limited, 2017)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, articles examine a diverse range of legal issues and their impact on and intersections with society. Topics covered: marriage equality and the demise of civil unions; the LGBTQ community in the 1980s; the landscape of choice regarding reproductive rights and vaccine refusal; the rights of unvaccinated children; a socio-legal framework for understanding the social control of pleasure; and a data re-use and its impact on group identity. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.
Prelims -- The emergence of marriage equality and the sad demise of civil unions --'Community Voices' and'Speaking Out' rights talk and the LGBTQ community in the 1980s -- Symposium health and the law: protection, promotion, paternalism.
Includes index.
Includes bibliographical references.
Keywords: Sociological jurisprudence; Law -- Political aspects; Law, Jurisprudence; Law & society